Prenatal diagnosis of congenital anomalies and birth institution complexity levels in Argentina - Astudillo, Analizia (2025)
Patiens with major congenital anomalies diagnosed prenatally should be referred to and delivered in institutions with the appropriate level of complexity, as this reduces morbidity and mortality. We aimed to assess the prevalence and prenatal diagnosis proportion of selected congenital abnormalities and the complexity levels of birth institutions in a sample of public maternity hospitals in Argentina. Data sources were (1) National Congenital Anomalies Registry, covering the period from 2013 to 2021; and (2) Categorization of birth institutions according to their complexity (high or low). Newborns with the following anomalies were selected for analysis: spina bifida, hydrocephalus, critical congenital heart defects, diaphragmatic hernia, gastroschisis, and omphalocele. Prevalences at birth and prenatal diagnosis proportions were calculated according to the birth institution complexity level. A total of 2.214.102 births across 131 institutions were evaluated, with 1.202.311 births in high-complexity institutions and 1.011.791 in low-complexity institutions. The prevalences per 10.000 births and the prenatal diagnosis proportions for the entire sample were: spina bifida 5,40(95%CI 5,10 − 5,71) 68,54%; hydrocephalus 6,96(95% CI 6,62 − 7,32) 78,92%; critical congenital heart defects 11,05(95% CI 10,62 − 11,49) 43,21%; diaphragmatic hernia 3,88(95%CI 3,62 − 4,14) 68,65%; gastroschisis 7,85(95%CI 7,48 − 8,22) 79,27%; omphalocele 2,01(95%CI 1,83 − 2,20) 76,18%. Prevalences and prenatal diagnosis porportions were significantly higher in high-complexity institutions. Prenatal diagnosis and perinatal care networks must be improved to ensure that patients with major congenital anomalies are delivered in high-complexity birth institutions. The prevalence and prenatal diagnosis porportion, stratified by the complexity level of institutions, can serve as management indicators to evaluate improvements in care quality.